The Location of Domestic and Foreign Production Affiliates by French Multinational Firms - Mejean, Isabelle (IMF Working Papers; Working Paper ;, 2010)
Economists interested in location choices usually focus their attention on investments abroad. This neglects the fact that multinational enterprises continue to invest domestically while undertaking foreign expansion. This paper compares investments at home and abroad. Our firm-level dataset shows an important home bias in productive investments. Part of this "excessive" domestic investment is explained by standard determinants of location choices. The interdependence between affiliates of the same industrial group however accounts for the lion's share of the home bias. Moreover, French firms' propensity to invest abroad is positively related to their productivity and the size of their intangible assets.